2019
DOI: 10.1111/ddi.12981
|View full text |Cite
|
Sign up to set email alerts
|

Impact of an invasive tree on arthropod assemblages in woodlots isolated within an intensive agricultural landscape

Abstract: Aim: Landscape simplification and the spread of invasive species are considered beyond the main threats to global biodiversity. It is well recognized that non-crop habitats bring complexity to farmland and provide refuge for a wide range of organisms, including arthropods. However, knowledge about the effects of invasive trees on arthropods in non-crop habitats in intensive agricultural landscapes is still weak. Therefore, we examined differences in the arthropod assemblages between woodlots formed by the inva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 79 publications
(145 reference statements)
1
5
0
Order By: Relevance
“…Furthermore, this study shows that while urban development is often seen as a facilitator of species invasion (e.g., MacDougall & Turkington, 2005), plant invasion has strong effects on the community composition of higher trophic levels independent of development. This is consistent with Elleriis, Pedersen, and Toft (2015) and Štrobl et al (2019) who reported robust effects of invasive plants on paired arthropod assemblages in temperate ecosystems in Continental Europe while accounting for site‐specific environmental variation. Hence, plant invasion is not just a side effect of urban development but also an important driver of ecological change.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Furthermore, this study shows that while urban development is often seen as a facilitator of species invasion (e.g., MacDougall & Turkington, 2005), plant invasion has strong effects on the community composition of higher trophic levels independent of development. This is consistent with Elleriis, Pedersen, and Toft (2015) and Štrobl et al (2019) who reported robust effects of invasive plants on paired arthropod assemblages in temperate ecosystems in Continental Europe while accounting for site‐specific environmental variation. Hence, plant invasion is not just a side effect of urban development but also an important driver of ecological change.…”
Section: Discussionsupporting
confidence: 90%
“…First, exotic plants can outcompete native flora for nutrients, space, and light, often decreasing the richness and abundance of native plant species (Castro‐Díez, Pauchard, Traveset, & Vilà, 2016; Michelan, Thomaz, Mormul, & Carvalho, 2010). Second, invasive plants can affect higher trophic levels within the local community, such as herbivorous arthropods, through changes in their food supply and quality (e.g., Štrobl et al, 2019) or modification of the local vegetation structure and microclimatic niches (Gerber et al, 2008; Litt, Cord, Fulbright, & Schuster, 2014; Valtonen, Jantunen, & Saarinen, 2006). Similar to urban development, invasive plants can drive functional homogenization of the vegetation (Castro‐Díez et al, 2016) as well as arthropod communities (Florencio, Cardoso, Lobo, Azevedo, & Borges, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Pitfall trapping was first used for the research of epigaeic fauna by Dahl (1896) and was further developed after the publication of Barber (1931) and Stammer (1948). It is now a well‐established and commonly used quantitative method of zoocoenosis surveys, including harvestman and millipede communities (Štrobl et al., 2019). Pitfall traps are simple to use, efficient, and inexpensive and allow for the continuous collection of specimens, including night foragers, thus overcoming interspecific differences in circadian activity rhythms (Koivula et al., 2003; Southwood, 1978; Törmälä, 1982; Ward et al., 2001).…”
Section: Introductionmentioning
confidence: 99%
“…Mid-field woodlots are small non-productive elements in agricultural landscapes that may serve as important biodiversity refuges (e.g., Tryjanowski et al, 2014;Štrobl et al, 2019;Pustkowiak et al, 2021). However, their role as distinctive landscape features has been largely overlooked (but see Gottschalk et al, 2010;Aue et al, 2014), since previous studies have included mostly all semi-natural landscape features together at the regional scale (Billeter et al, 2008;Doxa et al, 2010;Sasaki et al, 2020) or considered larger woodland patches from the perspective of forest habitat fragmentation (McCollin, 1993;Bellamy et al, 1996;Doherty and Grubb, 2000;Bennett et al, 2004;Lorenzetti and Battisti, 2006).…”
Section: Discussionmentioning
confidence: 99%